ANALISIS PARTISIPASI MASYARAKAT DALAM PROGRAM TRANSMIGRASI DI UNIT PERMUKIMAN TRANSMIGRAN (UPT) DESA UMPANGA KECAMATAN BUNGKU BARAT KABUPATEN MOROWALI - Salhudin, Salhudin (Katalogis, 2015)
This study aims to: (1) determine and analyze the participation of the community in terms of aspects of planning, implementation, and oversight in the transmigration program in UPT. Umpanga village, West of Bungku district, Morowali regency; and (2) determine the factors that support and obstacles in the public participation in transmigration program in UPT. Umpanga village, West of Bungku district, Morowali regency. The population of this study is all the community migrants who live in UPT. Umpanga village, West of Bungku district of Morowali regency as many as 125 families. These families consist of 70 families of TPS (Transmigration of Indigenous Peoples) and 55 families of TPA (Transmigration of Original People). As the relatively large number of population in this research, the researchers set a sample of 56 households using simple random sampling technique. Data were analyzed using qualitative descriptive analysis with frequency tables and triangulation. The results of this study indicate that community participation in terms of aspects of planning, implementation, and control have properly managed in the transmigration program in Unit of Transmigration Settlement (UPT) Village Umpanga District of Bungku West Morowali and factors that support community participation in the transmigration program in UPT. Umpanga village, including the motivation of citizens to involve in the transmigration program and the new jobs vacacies after the program has been implemented in the village. Meanwhile, the factors that impact the public to participate in the resettlement program in UPT. Umpanga village, include theÂ understanding of community regards to the transmigration program and the limited opportunities to participate because people are focused on to earn more money in order to fulfill their basic needs.